2015
DOI: 10.1007/s00468-015-1252-x
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum effect on starch, soluble sugar, and phytohormone in roots of Quercus serrata Thunb. seedlings

Abstract: Key message Glucose was a key substance as an energy source in the root growth promotion by Al, and ABA may relate to metabolism involved with its process. Abstract Generally, excess aluminum (Al) ions in soil solution are toxic to many cultivated plant species, but beneficial effects of Al for plant growth have been reported. Previously, we reported stimulation of root growth and nitrate reductase (NR) activity by Al. In this study, we focused on sugars, such as sucrose, glucose, and fructose, as energy sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 42 publications
3
20
0
5
Order By: Relevance
“…Similar results have been reported in other plants like maize [29], Quercus serrata [37] and Camellia sinensis [60]. In Quercus serrata , there was also an increase in the concentration of soluble sugars, especially glucose, as well as abscisic acid (ABA).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Similar results have been reported in other plants like maize [29], Quercus serrata [37] and Camellia sinensis [60]. In Quercus serrata , there was also an increase in the concentration of soluble sugars, especially glucose, as well as abscisic acid (ABA).…”
Section: Resultssupporting
confidence: 84%
“…In Quercus serrata , there was also an increase in the concentration of soluble sugars, especially glucose, as well as abscisic acid (ABA). This suggests that growth stimulation by Al involves a complex signaling network where glucose has a key role as an energy source and as a signaling molecule together with ABA, and might be related with carbon (C) and nitrogen (N) metabolism to induce root growth in response to Al [37]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…or other toxic metal ions, and the decrease in nutrient availability, and these changes may negatively affect tree growth (Hirano et al 2007). Moriyama et al (2016), however, suggested that Al had beneficial effects on root growth of Quercus serrata seedlings. In their experiments, the roots of the seedlings that were treated with Al also showed increased levels of nitrate reductase, soluble sugars such as glucose and abscisic acid, which could be involved in the increase of root growth.…”
mentioning
confidence: 99%